2020
DOI: 10.1038/s41416-020-01091-1
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HOTAIR regulates the invasion and metastasis of prostate cancer by targeting hepaCAM

Abstract: Background The role of HOX transcript antisense RNA (HOTAIR) has been proven to be important in tumorigenesis. However, how this molecule promotes metastasis and invasion in PCa is still unclear. Methods The relationship between HOTAIR and hepatocellular adhesion molecule (hepaCAM) in PCa was identified by immunohistochemistry, immunofluorescence, plasmid transfection, quantitative real-time PCR and immunoblotting. The regulatory effects of HOTAIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Literature indicates that the expression of HepaCAM expression is always reduced, or completely lost in many cancers, including prostate cancer. 13,14 However, systematic studies of CRPC are rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature indicates that the expression of HepaCAM expression is always reduced, or completely lost in many cancers, including prostate cancer. 13,14 However, systematic studies of CRPC are rare.…”
Section: Discussionmentioning
confidence: 99%
“…13 Furthermore, HOTAIR is known to inhibit HepaCAM transcription, thus promoting prostate cancer metastasis via MAPK signaling. 14 Numerous studies indicate that the HepaCAM gene acts as a tumor suppressor candidate that may be downregulated during cancer development. However, the actual pathological mechanism responsible for how HepaCAM affects the metastasis of prostate cancer has not been fully elucidated, particularly in castrationresistant cancer cell types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the epigenetic modulation manners, histone methylation modification exerts multiple effects on gene transcription (13)(14)(15). Methylation modification at some specific lysine activates gene transcription, and whereas methylation modification at other lysine represses gene transcription, such as the classical repressive histone marker tri-methylation of histone H3 at lysine 27 (H3K27me3) (16)(17)(18). In our previous study, we found an HCC-related histone lysine methyltransferase NSD1 (nuclear receptor binding SET domaincontaining protein 1), which catalyses di-methylation of histone H3 at lysine 36 (H3K36me2) (19).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lncRNA LEF1-AS1 upgrades androgen-independent PCa progression via the upregulation of FZD2 and CD44 14 and lncRNA HOTAIR advances the invasion and metastasis of PCa by activating MAPK pathway. 15 …”
Section: Introductionmentioning
confidence: 99%